The development, conceptualisation and implementation of quality in disability support services - Šiška, Jan; Beadle-Brown, Julie (Charles University, Karolinum Press, 2021)
Social services for people with disabilities have undergone substantial changes over time, in particular in the past two decades. Whilst lack of affordable and appropriate housing is a barrier to community living for many people with disabilities, it is only one part of the jigsaw. This book traces some of these changes, in particular related to living situation and support available, in a range of different countries and considers the factors that have influenced these changes. This book considers other aspects of what is needed to bring about real change in the lives of all people with disabilities.